EFFECT OF POSTURE ON MAXIMUM AND AVERAGE FLOWRATES ON UROFLOWMETRY OF MALES WITH VOIDING LOWER URINARY TRACT SYMPTOMS: A RANDOMIZED CONTROL CLINICAL TRIAL (The Research of Medical Science Review, 2024)
Background: Benign prostatic hyperplasia (BPH) is a common cause of lower urinary tract symptoms (LUTS) in men. Uroflowmetry is a diagnostic tool used to evaluate LUTS, and voiding position may affect uroflowmetric parameters. This study aimed to investigate the effect of standing and sitting voiding positions on uroflowmetric findings and post-void residual volume in men with BPH. Methods: A randomized controlled trial was conducted with 90 patients with BPH, divided into two groups: standing and sitting voiding positions. Uroflowmetry was performed using the MMS Flowmeter Device, and maximum flow rate (Qmax), average flow rate (Qavg), and post-void residual (PVR) volume were recorded. Results: The results showed that Qmax was significantly higher in the sitting posture (12.14 mL/s) compared to the standing posture (10.2 mL/s) (p = 0.017). Qavg was also higher in the sitting posture, although the difference was not statistically significant (p = 0.056). There was no significant difference in PVR volume between the two groups. Conclusion: This study demonstrated that voiding in a sitting position results in significantly higher Qmax compared to standing in men with BPH. Incorporating a sitting position into BPH management may have a synergistic effect in improving urinary flow.